2016
DOI: 10.5534/wjmh.2016.34.1.40
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Medical Treatment of Peyronie's Disease: Potassium Para-Aminobenzoate Monotherapyvs.Combination Therapy with Tamoxifen, L-Carnitine, and Phosphodiesterase Type 5 Inhibitor

Abstract: PurposeThis study was designed to evaluate the efficacy of medical treatment of Peyronie's disease.Materials and MethodsA total of 109 patients with Peyronie's disease who had been treated from January 2011 to December 2014 were retrospectively reviewed in this study. Forty-four patients (Group 1) were treated with 12 mg of potassium para-aminobenzoate daily. Sixty-five patients (Group 2) were treated with combination therapy: tamoxifen (20 mg) and acetyl-L-carnitine (300 mg) twice daily in addition to a phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Previous clinical studies have shown mixed results using PDE5i and SERMs [33][34][35][36][37]. An open-label single-arm study with tamoxifen showed a positive effect [33], while a later placebo-controlled study showed no effect with tamoxifen [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous clinical studies have shown mixed results using PDE5i and SERMs [33][34][35][36][37]. An open-label single-arm study with tamoxifen showed a positive effect [33], while a later placebo-controlled study showed no effect with tamoxifen [34].…”
Section: Discussionmentioning
confidence: 98%
“…However, the open-label study noted that tamoxifen showed some improvement in patients with early PD [33], while all the patients in the latter study were in the late phase of the disease [34]. Similarly, in studies with PDE5i, the results have been mixed [35][36][37]. This is not surprising since the drugs were tested on patients with established plaque-fibrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The result on pain reduction is striking when compared to the sham group and with the historical results of steroids and ant-inflammatory drugs from the literature [3] .…”
Section: Discussionmentioning
confidence: 75%
“…Many oral therapies have been used for the treatment of PD, that is, vitamin E, potassium para-aminobenzoate, tamoxifen, colchicin, carnitine, and pentoxifylline [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Park et al . report on Potaba versus combination therapy of tamoxifen, l -carnitine, and tadalafil 19 . Perhaps the most striking result was that two-thirds of the patients in the Potaba arm withdrew for varying reasons, although treatment side effects were cited as the largest single factor.…”
Section: Pharmacotherapymentioning
confidence: 99%